International variation in phytosanitary legislation and regulations governing importation of plants for planting. Issue 51 (August 2015) - Eschen, R.; Britton, K.; Brockerhoff, E.; Burgess, T.; Dalley, V.; Epanchin-Niell, R.S.; Gupta, K.; Hardy, G.; Huang, Y.; Kenis, M.; Kimani, E.; Li, H.-M.; et al.
Highlights: All reviewed countries stipulate a unique set of phytosanitary measures. Only phytosanitary certificates and import inspection are required by all countries. Little is known about quality of implementation and impact of individual measures. Abstract: The trade in plants for planting (P4P) is one of the major pathways for the introduction of pests. The strong increase in world trade in the past decades appears to have led to an increase in introductions of species transported by this pathway, and highlights the need for effective phytosanitary legislation and measures. The phytosanitary regulations in most countries are based on the International Plant Protection Convention and the World Trade Organisation's Agreement on Sanitary and Phytosanitary Measures, but there are large differences in countries' approaches to managing the risk of introducing invasive alien species through international plant trade. We reviewed elements of the phytosanitary legislations of ten countries on all continents and aimed to find regulations that prevent biological invasions. We found large differences in countries' phytosanitary regulations. New Zealand and Australia have the strictest phytosanitary regulations, while Europe maintains a general authorization for P4P imports. The remaining countries have regulations between these extremes. The evidence is sparse regarding the quality of implementation and effectiveness, and impact of individual phytosanitary measures. We recommend that National Plant Protection Organisations collect detailed information on P4P imports and the effectiveness of phytosanitary measures. Such information could provide a basis to improve a country's phytosanitary regulatory framework or could be used in risk assessments.